(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
The indigenous peoples had received the most significant development within international law when their rights have been recognized under the United Nations Declaration on the Rights of Indigenous Peoples in 2007. However, the scope of the right to self-determination is still unresolved. This article aims to analyse the status of self-determination of the Mah Meri, an indigenous group in Kampung Sungai Bumbun, Pulau Carey. This study reveals that the Mah Meri face constraints to practice self-determination. Despite existing legal provisions and an agency dedicated to their welfare, the lackadaisical attitude of this group to improve on their standard of living, has resulted in their current backwardness. Thus, this article proposes that the indigenous peoples, particularly in Kampung Sungai Bumbun should be given the freedom to make decide on their way of life, with the state agency acting as a care taker without interfering into their traditional way of life. Keywords: Indigenous peoples, orang asli, aboriginal peoples, selfdetermination, international laws